DEVELOPING TOURING PLAN USING GEOGRAPHIC INFORMATION SYSTEM BASED ON VISUAL, NATURAL, AND CULTURAL QUALITIES IN PARANGTRITIS COASTAL AREA, YOGYAKARTA, INDONESIA - Setiawaty, Meity; Nurisjah, Siti; Suharnoto, Yuli (http://arl-faperta.ipb.ac.id/, 2010)
The objectives of this study is studying on developing touring plan in coastal area of Parangtritis based on its visual, natural, and cultural quality assessment. Those three aspects of quality are used as the basic consideration for site assessment in acquiring the potential tourism area, which is subsequently used in developing a touring system.Scenic Beauty Estimation (SBE) method and visual character variables assessment are used in assessing the visual quality of the study area. The technique of potential zones mapping applied by Gunn (1994) combined with cartographic regionalization (Smith, 1989) are used in assessing both natural and cultural quality of the area.In general, Parangtritis is dominated with high to medium quality of potential area for tourism, which includes beach, sand dunes, woodlands, and a big part of agriculture area. Based on potential area and existing tourism objects, there are three track alternatives that have been developed in this study by using the concept of developing an interpretive track, as adopted from Damayanti (2003).According to the prioritizing process using Analytical Hierarchy Process (AHP), the third alternative of touring plan, whichhas the highest priority for the criteria of educational benefits, is perceived to be the most preferable alternative as the potential tourism network in Parangtritis Coastal Area.